COMPLIANCE OF NIGERIAN UNION OF ROAD TRANSPORT WORKERS (NURTW) WITH BAN ON ALCOHOL SALES IN MOTOR PARKS: IMPLICATIONS FOR ACCIDENT REDUCTION AMONG COMMERCIAL DRIVERS IN OSUN STATE - AYODELE, R.B.; OLUBAYO-FATIREGUN, M.A. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
This study examined compliance of Nigeria Union of Road Transport Workers (NURTW) with ban on sale of alcohol in motor parks and its implications for accident reduction among commercial drivers in Osun State. This study used a descriptive survey design. Sixteen major NURTW units in Osun State were selected by stratification, based on locations (urban and rural). From each group, 2 locations were sampled by convenience. All the 16 major units in the four locations and their Chairmen were sampled intact. Controlled observation and validated questionnaire were used to gather data for the study. The former was used to ascertain the compliance status of NUR1W with the ban on alcohol sales, while the latter examined the number of accidents involving commercial drivers in each NUR1W unit since the ban. Data were analysed using percentage and t-test. Results indicated that the compliance score for NURTW units in the rural locations was 19 (Mean = 4.75), while the compliance score for those in the urban was 21 (Mean = 1.75). No significant difference was found between the numbers of accidents involving drivers from compliant and non-compliant units. It was concluded that NURTW units in the urban locations do not comply with ban on sales of alcohol, while their rural counterparts complied and that the ban does not reduce the commercial drivers involvement in road accidents. A review of existing regulations, enforcement and safety education of drivers were recommended.